2020
DOI: 10.1002/asia.202000666
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of Axial Anisotropy in a 1D Coordination Polymer shows Improved Field Induced Single Molecule Magnet Behavior over a Mononuclear Seven Coordinated FeII Complex

Abstract: Herein, we report a CN‐bridged alternating FeII−NiII 1D chain to ensure the alignment of axial anisotropy and improve the single molecule magnet (SMM) behavior in seven coordinated FeII compound. The chain was constructed from hepta coordinated Fe(II) complex as an anisotropic building unit and diamagnetic nickel tetra cyanate as a bridging ligand. The magnetic measurements show the easy‐axis anisotropy of the seven coordinated Fe(II) complex and field induced SMM behavior with spin reversal energy barrier Uef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…7) and thus align the directions of the easy axis of all Fe centers in the same direction. 70,72 SMM behavior characterized by U eff /k B = 49 K was obtained for [Fe(L1 Ph ){Ni(CN) 4 }] whereas only fast relaxation was observed for [Fe(L1 Ph )Cl 2 ] that exhibits a very similar magnetic anisotropy but a crystal packing of tilted molecules. 70 From Table 4 it can be observed that U eff /k B may vary substantially even for complexes exhibiting similar magnetic anisotropy.…”
Section: I6 D 6 Ions (Fe Ii )mentioning
confidence: 99%
“…7) and thus align the directions of the easy axis of all Fe centers in the same direction. 70,72 SMM behavior characterized by U eff /k B = 49 K was obtained for [Fe(L1 Ph ){Ni(CN) 4 }] whereas only fast relaxation was observed for [Fe(L1 Ph )Cl 2 ] that exhibits a very similar magnetic anisotropy but a crystal packing of tilted molecules. 70 From Table 4 it can be observed that U eff /k B may vary substantially even for complexes exhibiting similar magnetic anisotropy.…”
Section: I6 D 6 Ions (Fe Ii )mentioning
confidence: 99%
“…More importantly, using a building-block synthetic approach with selected capping ligands, the cyanometallate molecular precursors are allowed to self-assemble toward desired structural architectures ranging from discrete molecules to extended systems . These characteristics enable the cyanometallate compounds as promising candidates for versatile molecule-based materials including single-molecule magnets (SMMs), single-chain magnets (SCMs), magnetic ordering complexes, and spin-transition materials …”
Section: Introductionmentioning
confidence: 99%
“…However, in complex 2 , as there are two crystallographic unique Fe 2 II Mo III units (A and B, see above) connected to each other by H-bonds, the anisotropy axes of the Fe II ions (assumed to be along the O–Fe–N cyanide direction) point to different directions (Figure S14). The arrangements of the anisotropic axes of Fe II ion in 1 might contribute to suppressing the spin–lattice relaxation (QTM, direct, and Raman) accompanied by the thermally activated (Orbach) processes, while, the different orientations of the anisotropy axes in 2 lead to a rapid relaxation. ,, …”
Section: Results and Discussionmentioning
confidence: 99%